Implementation of optimal strategy to economically improve batch membrane separation. (April 2019) - Sharma, Ayush; Valo, Richard; Kalúz, Martin; Paulen, Radoslav; Fikar, Miroslav
Graphical abstract: Highlights: Application of control theory to optimize membrane separation process. Implementation of the optimal strategy to concentrate product and reduce impurity. Advantages of optimal strategy over implemented classical counterparts described. Experiments presented to show the effect of initial/final concentrations over results. The strategy is applicable for other filtering problems with current industrial setup. Abstract: In this paper, optimal strategy based on Pontryagin's minimum principle is presented for batch membrane separation of lactose-salt water solution, whilst minimizing costs. Optimal control problem comprises a weighted combination of the processing time and diluant consumption, i.e., the overall processing cost of separation. Process model is derived from mass balance and its parameters are estimated using dynamic least-squares procedure from process data. Nanofiltration plant is used to verify and critically review the proposed optimal, and standard industrial strategies. In comparison to the standard strategies, optimal strategies reduce the batch time up to 8% and the diluant consumption up to 25%.